Formulation and evaluation of stability of thai purple rice bran-based cosmetic products - Chaiyavat Chaiyasut (2018)
© 2018 The Authors. Objective: The rice bran (RB) phytochemicals are known for several pharmacological properties. The current study was aimed to extract the active principles from Thai purple RB, formulate the cosmetic products, and evaluate the physical property and stability of the products. Methods: Purple RB was extracted using 80% ethanol, and total phenolic and anthocyanin contents were measured using high-pressure liquid chromatography (HPLC) and spectrophotometric methods. Rice bran oil (RBO) was obtained by cold press method, and oryzanol content was determined using HPLC. The antioxidant capacity of RBO and purple rice bran extract (PRE) was assessed using spectrophotometric methods. The cosmetic products were formulated with PRE and fermented and distilled purple rice solution (FDPRS). RBO was also used as an ingredient in the formulation of solid soap. The stability of the formulations was also assessed. The heavy metal and microbial contamination were determined using atomic absorption spectrometry and plating assay, respectively. Results: The yield of PRE and RBO was 0.92 and 1.62%, respectively. The total phenolic and anthocyanin content of PRE was 305.30±6.15 mg gallic acid/g of extract and 877.33±87.73 mg cyanidin chloride/g of extract, respectively. Oryzanol content of RBO was 6.33±0.09 mg/g of RBO. RBO, PRE, and FDPRS exhibited high antioxidant capacity. The cosmetic formulations were observed to be physically stable in the heat–cool cycle, and the stability of the active compounds was not affected while stored at 30°C for 2 months. The storage temperature affected the phenolic compounds present in the cosmetic formulations, especially at 45°C. There was no significant decrease in oryzanol content of soap formulation. All the formulations were free from microbial and heavy metal contamination. Conclusion: The RB phytochemical-based cosmetic products are rich in antioxidants, stable, and free from heavy metals and microbial contamination, and further fine-tuning of the formulation may achieve the market quality.